Affinity Chromatography Methods and Protocols - Reichelt, Senta.; Reichelt, Senta. (Methods in Molecular Biology, 2015)
The aim of this edition is to introduce the beginner to the basics of affinity chromatography and provide practical knowledge for the development of affinity separation protocols. Affinity Chromatography: Methods and Protocols, Third Edition guides readers through new state of the art protocols,  molecular modelling,  and the study of ligand-target interactions. Written in the successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls.     Authoritative and easily accessible, Affinity Chromatography: Methods and Protocols, Third Edition is  designed as a useful resource for those interested in the rapid and quantitative isolation of biomolecules with high purity.